Derma fillers: Ray of light in black triangles – A pilot study - Shalini Kapoor; Anjali Dudeja (Contemporary Clinical Dentistry, 2020)
Background and Aim: Open gingival embrasure often poses complex functional and esthetic problems. Interdental papilla reconstruction is among the most challenging periodontal treatments. Hyaluronic acid (HA) gel injection, a noninvasive technique with immediate papilla reconstruction, has been recently proposed. This minimally invasive therapeutic procedure has shown predictable esthetic outcome, thus, gaining rapid acceptance as an esthetic treatment modality in dentistry. The aim of the study is to evaluate the clinical application of derma fillers (HA gel) for the reconstruction of the interdental papilla in the esthetic zone. Materials and Methods: Six patients were included with interdental papilla deficiency. After the induction of local anesthesia, 0.2 ml of 0.2% HA injection was given at baseline, 3 weeks and 3 months. Measurements of the black triangle were done clinically using acrylic stent as a reference. The application of HA gel for the reconstruction of interdental papilla was found successful at a 6-month period. Results: The study showed a significant gain in papillary volume, and esthetics improvement was notable. A statistically significant result was obtained in context to papilla fill. Conclusion: Interdental papilla reconstruction with injectable HA gel is a promising minimally invasive treatment option for interdental deficiency in small areas.